UMA ANÁLISE DAS DEZ FALÁCIAS DO DESENVOLVIMENTO NA AMÉRICA LATINA - Bomfim, Brunno Leonarczyk; Cenci, Daniel Rubens; Pinto, Raquel Cristiane Feistel (Salão do Conhecimento, 2017)
Projeto de Iniciação Científica